Analysis of the Negotiation Process of PT Surya Bratasena Plantation with Pangkalan Kuras District, Pelalawan Regency - Ramadhany, Medina; Novel, Nurillah Jamil Achmawati; Safa’atul Barkah, Cecep (Universitas Muhammadiyah Yogyakarta, 2021)
The negotiation process is found in many situations, both professional and non-professional. Thus, negotiations now do not occur only in the scope of business related to buying and selling products and services. Negotiation occurs when there are two or more parties who work together to resolve a problem involving the negotiating parties. Generally, one party has something that the other party wants and the other party is willing to negotiate about it. The resolution of the PT Surya Bratasena Plantation problem with Pangkalan Kuras District is an example of conflict resolution through a negotiation process. In this paper, the researcher examines and analyzes the negotiation process carried out by PT Surya Bratasena Plantation in resolving land conflicts.